ANALISIS KEMAMPUAN ARGUMENTASI ILMIAH PESERTA DIDIK PADA MATERI PERUBAHAN LINGKUNGAN KELAS X DI MAN 2 TANAH DATAR - Putri, Mayang; Fadilah, Muhyiatul; Fuadiyah, Sa’adiyatul; Anggriyani, Ria (Universitas Cokroaminoto Palopo, 2024)
The problem in MAN 2 Tanah Datar states that there has never been a measurement of scientific argumentation ability and there is no data on students' scientific argumentation ability, especially on environmental change material. The purpose of this study was to determine the level of students' scientific argumentation ability on environmental change material with a descriptive research type. The sample used was 160 students who were taken using purposive sampling technique. The research instrument was in the form of five essay questions. Data analysis techniques were scoring, determining values ​​and determining the level of scientific argumentation. Of the 160 samples, there were 140 students whose scientific argumentation ability was categorized as sufficient and 20 students were categorized as weak. The overall results of the study showed that the level of students' scientific argumentation ability on environmental change material at MAN 2 Tanah Datar was classified as sufficient with a percentage of 42.63.